Preparation of Ca-Mg Double-Doped Mesoporous Silica Nanoparticles and Their Drug-Loading and Drug-Releasing Properties - Qian Zhang; Jiamin Huang; Chao Liu; Ruihua Chen; Tao Jiang; Yusufu Hailili; Telieke Bahetibieke; Xiaohui Tang; Mei Wang (Inorganics)
Breast cancer is a common clinical malignant tumor that seriously threatens women’s physical and mental health. Chemotherapy, as the first choice of breast cancer treatment, has limited its application in the clinic due to problems of poor stability, short half-life, and serious toxic side effects. With the emergence of nanotechnology, inorganic materials to prepare mesoporous silica nanoparticles (MSNs) have been widely used in anti-tumor drug carriers. However, their slow degradation rate limits their application in the biomedical field. Therefore, developing low-toxicity MSNs with good biocompatibility, biodegradability, and rapid release at the tumor site is a key scientific issue to be addressed. Here, we prepared DOX-loaded Ca-Mg-doped MSNs by electrostatic adsorption to obtain Ca-Mg@DOX@MSNs with suitable particle sizes and zeta potential, and the incorporation of calcium and magnesium also led to an increase in the degradation rate under acidic conditions and an accelerated release, which reduced the toxicity of DOX and promoted cellular uptake with good anti-tumor effects. This study provides a new idea for the clinical treatment of breast cancer.